Factors that affect utilization of antenatal care among recently pregnant women in three southern Africam countries: focus on the role of intimate partner violence - Chikovore, Emma Shuvai; Maharaj, Pranitha; Edmeades, Jeffrey (DHS Working Papers No. 198, 2024)
Intimate partner violence (IPV) has significant negative consequences for pregnant women and, when considered with other factors, can affect the utilization of antenatal care. The objective of this study is to identify the relationship between the use of antenatal care (ANC) and IPV around the time of the most recent pregnancy among women age 15 to 49. Cross-sectional data from the most recent Demographic and Health Survey of three countries—Malawi, Zambia, and Zimbabwe—were analyzed. Data were obtained from 3,479 women age 15–49 who answered the domestic violence module. The study found the following: Zimbabwe had the highest percentage of women who received the recommended number of ANC visits (70.4%), while Malawi had the lowest percentage (47.6%). The highest percentages of women with the recommended number of visits were found among the 20–24-year-age group in all three countries: Malawi (33.3%), Zambia (28.9%), and Zimbabwe (27.6%). Zimbabwean women with autonomy had 2.5 times the odds of having the recommended ANC visits compared to those without autonomy (OR: 2.5, 95% CI [1.64, 3.91], p < .001). Women who reside in rural areas in Malawi had 50% lower odds of having the recommended ANC visits (OR: 0.5, 95% CI [0.32, 0.82], p < .01). Women with four or more children had lower odds of having the recommended ANC visits in all countries. In Zambia, women who had experienced IPV in the previous 12 months had lower odds of having the recommended ANC visits (OR: 0.66, 95% CI [0.50, 0.88], p < .01). The study concludes that the experience of IPV does not appear to influence the utilization of the recommended ANC visits in two of the three countries. Although number of children ever born seemed to be commonly associated with having the recommended ANC visits in all three countries, all other factors were context specific. It is important to identify context-specific factors such as IPV that may impede ANC utilization and to address unnecessary complications that are directly associated with minimum use of ANC services.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was conducted with support from the United States Agency for International Development (USAID) through The DHS Program (#720-OAA-18C-00083). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.